Fish Cytogenetic Techniques: Ray-Fin Fishes and Chondrichthyans - Ozouf-Costaz, Catherine; Pisano, Eva; Foresti, Fausto [UNESP]; de Almeida Toledo, Lurdes Foresti (Taylor & Francis, 2015)
Recent advances in fish cytogenetics have enhanced the interest in chromosome analysis in both fundamental (systematics and comparative genomics among fishes and other vertebrate groups) and applied (aquaculture, conservation and response to pollutants, whole genome sequencing of model fish species) research. Although the genomic material, the chro.